2014
DOI: 10.1155/2014/413249
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Levels of Inflammatory Mediators and Low Frequency of Regulatory T Cells in the Peripheral Blood of Preeclamptic Mexican Women

Abstract: Regulatory T cells (Tregs; CD4+CD25highFoxp3+) are critical in maintaining immune tolerance during pregnancy and uterine vascularization. In this study, we show that, in Mexican women with different preeclamptic severity levels, the number of Tregs and the subset of CD4+CD25highFoxp3+ are decreased compared with those of normotensive pregnant women (NP). Moreover, a systemic inflammatory state is a pivotal feature in the pathogenesis of this disorder and could be related to hypertension and endothelial dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
(46 reference statements)
1
33
0
Order By: Relevance
“…There is controversy with respect to the concentrations of these proteins in PE [21][22][23][24][25][26][27][28]. On the other hand, we observed that the maternal concentrations of VCAM-1 were higher in PE.…”
Section: Discussionmentioning
confidence: 61%
“…There is controversy with respect to the concentrations of these proteins in PE [21][22][23][24][25][26][27][28]. On the other hand, we observed that the maternal concentrations of VCAM-1 were higher in PE.…”
Section: Discussionmentioning
confidence: 61%
“…Circulating TNF-α levels are increased in PE compared with Norm-Preg women (Moreno-Eutimio et al, 2014; Pinheiro et al, 2015; Cakmak et al, 2016), although the placental levels of TNF-α may not be different in PE versus normal pregnancy (Peixoto et al, 2016). LIGHT, a TNF superfamily member, is also increased in PE and may contribute to placental damage and ischemia (Wang et al, 2014).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 95%
“…IL-6 is a pro-inflammatory cytokine that may also be elevated in PE (Ramma et al, 2012; Moreno-Eutimio et al, 2014). RUPP rats show increased plasma levels and higher CD4 + T cell production of IL-6 (Wallace et al, 2011; Cornelius et al, 2015), and infusion of IL-6 leads to HTN and proteinuria in pregnant rats (Lamarca et al, 2011).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 99%
“…Placental ischemia may enhance the release of inflammatory cytokines such as tumor necrosis factor-α (TNFα) and interleukin-6 (IL-6) [9698]. Circulating TNFα levels are increased in preeclamptic vs normal Preg women [108110], and the plasma levels and CD4 + T cell production of TNFα are increased in RUPP vs Preg rats [98, 111, 112]. TNF-α may modify the expression of adhesion molecules in placental vessels [98] and may contribute to abnormal MMP production in preeclampsia.…”
Section: Discussionmentioning
confidence: 99%